Semiotics of the study room in the russian novel of the second half of the 19th century - Няголова, Наталия (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The article discusses the semiotic parameters of the locus of the study room in the Russian novel from the second half of the 19th century. It outlines the socio-cultural context that makes this locus topical in the works of the Russian novelists from the epoch after the reforms. The given examples of presence of the study room in the novels of I. Turgenev, I. Goncharov, F. Dostoevsky and L. Tolstoy are interpreted in several principle aspects: – objects in the composition and its selection – the relation character – material detail – semantic transformations and their motivation.